Scorpion Venom Heat-Resistant Peptide Protects Transgenic Caenorhabditis elegans from β- Amyloid Toxicity - Xiao-Gang Zhang; Xi Wang; Ting-Ting Zhou; Xue-Fei Wu; Yan Peng; Wan-Qin Zhang; Shao Li; Jie Zhao; Jie Zhao (Frontiers Media S.A., 2016)
Scorpion venom heat-resistant peptide (SVHRP) is a component purified from Buthus martensii Karsch scorpion venom. Our previous studies found SVHRP could enhance neurogenesis and inhibit microglia-mediated neuroinflammation in vivo. Here, we use the transgenic CL4176, CL2006 and CL2355 strains of Caenorhabditis elegans which express the human Aβ1-42 to investigate the effects and the possible mechanisms of SVHRP mediated protection against Aβ toxicity in vivo. The results showed that SVHRP-fed worms displayed remarkably decreased paralysis, less abundant toxic Aβ oligomers, reduced Aβ plaque deposition with respect to untreated animals. SVHRP also suppressed neuronal Aβ expression-induced defects in chemotaxis behavior and attenuated levels of ROS in the transgenic C. elegans. Taken together, these results suggest SVHRP could protect against Aβ-induced toxicity in C. elegans. Further studies need to be conducted in murine models and humans to analyze the effectiveness of the peptide.